PIKHER2: A phase IB study evaluating buparlisib in combination with lapatinib in trastuzumab-resistant HER2-positive advanced breast cancer. (November 2017) - Guerin, Mathilde; Rezai, Keyvan; Isambert, Nicolas; Campone, Mario; Autret, Aurélie; Pakradouni, Jihane; Provansal, Magali; Camerlo, Jacques; Sabatier, Renaud; Bertucci, François; Charafe-Jauffret, Emmanuelle; Hervieu, Alice; et al.
Abstract: Background: Phosphatidylinositol 3-kinase (PI3K)/AKT/mammalian target of rapamycin pathway is frequently activated in HER2-positive breast cancer and may play a major role in resistance to trastuzumab. Buparlisib is a pan-class-I PI3K inhibitor with potent and selective activity against wild-type and mutant PI3K p110 isoforms. Patients and methods: PIKHER2 phase IB study aimed primarily to determine a maximum tolerated dose (MTD) and propose a recommended phase II dose (RP2D) for buparlisib in combination with lapatinib in HER2-positive, trastuzumab-resistant, advanced breast cancer. Oral buparlisib (40, 60 or 80 mg) and lapatinib (750, 1000 or 1250 mg) were administered daily. A modified continuous reassessment method using an adaptive Bayesian model guided the dose escalation of both agents. Secondary end-points included antitumour activity and pharmacokinetic (PK) assessments. Results: A total of 24 patients were treated across five dose levels. Dose-limiting toxicities included transaminases elevation, vomiting, stomatitis, hyperglycemia and diarrhoea. MTD was declared at buparlisib 80 mg/d + lapatinib 1250 mg/d, but toxicities and early treatment discontinuation rate beyond cycle 1 led to select buparlisib 80 mg + lapatinib 1000 mg/d as the RP2D. Main drug-related adverse events included diarrhoea, nausea, skin rash, asthenia, depression, anxiety and transaminases increase. There was no significant evidence for drug–drug PK interaction. Disease control rate was 79% [95% confidence interval [CI] 57–92%], one patient obtained a complete remission, and six additional patients experienced stable disease for ≥ 24 weeks (clinical benefit rate of 29% [95% CI 12–51%]). Conclusion: Combining buparlisib and lapatinib in HER2-positive trastuzumab-resistant advanced breast cancer was feasible. Preliminary evidence of antitumour activity was observed in this heavily pre-treated population. Trial registration ID: NCT01589861 . Highlights: Evaluation of buparlisib–lapatinib combination in resistant HER2-positive advanced breast cancer. We examined the safety and tolerance and proposed a recommended phase II dose. No significant pharmacokinetic drug–drug interaction was found. Preliminary evidence of clinical activity was observed.